Conflict and housing, land and property rights: a handbook on issues, frameworks, and solutions - Leckie, Scott (Cambridge University Press, 2011)
Introduction to the issues - HLP rights and sustainable peace -- The international HLP rights normative framework -- Displacement, conflict and HLP rights -- HLP restitution rights : theory, law and concepts -- Restitution mechanisms and institutional frameworks -- United Nations and other peace operations and HLP rights -- Protracted displacement and political obstacles to the protection of HLP rights -- Emerging conceptual issues -- Improving international responses to HLP rights and conflict : the work of NGOs in the HLP rights field.